Evidence of commitment to research partnerships? Results of two web reviews - de Moissac, Danielle; Bowen, Sarah; Botting, Ingrid; Graham, Ian D; MacLeod, Martha; Harlos, Karen; Songok, Charity M; Bohémier, Monique (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Partnerships between academic researchers and health system leadership are often promoted by health research funding agencies as an important strategy in helping ensure that funded research is relevant and the results used. While potential benefits of such partnerships have been identified, there is limited guidance in the scientific literature for either healthcare organisations or researchers on how to select, build and manage effective research partnerships. Our main research objective was to explore the health system perspective on partnerships with researchers with a focus on issues related to the design and organisation of the health system and services. Two structured web reviews were conducted as one component of this larger study. Methods Two separate structured web reviews were conducted using structured data extraction tools. The first review focused on sites of health research bodies and those providing information on health system management and knowledge translation (n = 38) to identify what guidance to support partnerships might be available on websites commonly accessed by health leaders and researchers. The second reviewed sites from all health ‘regions’ in Canada (n = 64) to determine what criteria and standards were currently used in guiding decisions to engage in research partnerships; phone follow-up ensured all relevant information was collected. Results Absence of guidance on partnerships between research institutions and health system leaders was found. In the first review, absence of guidance on research partnerships and knowledge coproduction was striking and in contrast with coverage of other forms of collaboration such as patient/community engagement. In the second review, little evidence of criteria and standards regarding research partnerships was found. Difficulties in finding appropriate contact information for those responsible for research and obtaining a response were commonly experienced. Conclusion Guidance related to health system partnerships with academic researchers is lacking on websites that should promote and support such collaborations. Health region websites provide little evidence of partnership criteria and often do not make contact information to research leaders within health systems readily available; this may hinder partnership development between health systems and academia.